Influence of Br-substitution on the physical properties of cesium lead iodides - Kumar M.; Pawar V.; Jha P.A.; Jha P.K.; Singh P. (My University, 2025)
In this work, CsPbI3 and CsPbBr0.5I2.5 were synthesized by the cold sintering method. The structural studies were verified using X-ray diffraction with Rietveld refinement and revealed the orthorhombic phase with Pnma symmetry. Moreover, the crystallite size and the microstrain of the samples reduced with the Br- substitution. Scanning Electron Microscopy showed the regular form of grain size for CsPbI3, but CsPbBr0.5I2.5 shows the dense morphology with voids. The XPS spectra of the materials revealed the constituent's elemental details. UV-Visible measurements revealed the absorbance spectra of the samples and the bandgap energy from Tauc's relation is found to be ∼2.33 eV. © 2020 Author(s).